Analysis of Specialists' Opinions on the Issue of Special Physical Training of Junior Waterpolo Swimmers depending on the Playing Position - Andrei Cavcaliuc (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
Currently, optimizing the training process, in particular the special physical training of junior waterpolo swimmers is a complex and important challenge in performance sports. The subject of the research is solving the problem of the special physical training of junior waterpolo swimmers, which requires integrated and personalized approaches, taking into account the individual needs of the athletes depending on the playing position and the specific requirements of the event. In order to achieve a complete and detailed picture of the investigated subject, the following research methods were used: the study of bibliographic materials, pedagogical observation, the questionnaire, and conversations with specialists in the field. The obtained results show that the specialists in the field are of the opinion that special physical training must have an important role in the training of junior water polo swimmers in the water polo competition, a fact that requires the creation of specific characteristics for the playing position.